2012
DOI: 10.1111/tpj.12035
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear ubiquitin proteasome degradation affects WRKY45 function in the rice defense program

Abstract: The transcriptional activator WRKY45 plays a major role in the salicylic acid/benzothiadiazole-induced defense program in rice. Here, we show that the nuclear ubiquitin–proteasome system (UPS) plays a role in regulating the function of WRKY45. Proteasome inhibitors induced accumulation of polyubiquitinated WRKY45 and transient up-regulation of WRKY45 target genes in rice cells, suggesting that WRKY45 is constantly degraded by the UPS to suppress defense responses in the absence of defense signals. Mutational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 48 publications
(76 reference statements)
2
126
0
Order By: Relevance
“…Interactions between NLRs and WRKY TFs, which are involved in defense signal transduction, have also been reported in plants. For example, MLA10 interacts with HvWRKY1 and HvMYB6 (Shen et al, 2007;Chang et al, 2013), Pb1 interacts with WRKY45 Matsushita et al, 2013), and Xa21 interacts with WRKY62 (Peng et al, 2008;Park and Ronald, 2012). We observed that the transcript levels of WRKY46 and WRKY72 differed, suggesting that WRKY72 may be directly involved in the defense response signaling pathway while WRKY46 contributes in some other way (Supplemental Figure 13).…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 57%
See 1 more Smart Citation
“…Interactions between NLRs and WRKY TFs, which are involved in defense signal transduction, have also been reported in plants. For example, MLA10 interacts with HvWRKY1 and HvMYB6 (Shen et al, 2007;Chang et al, 2013), Pb1 interacts with WRKY45 Matsushita et al, 2013), and Xa21 interacts with WRKY62 (Peng et al, 2008;Park and Ronald, 2012). We observed that the transcript levels of WRKY46 and WRKY72 differed, suggesting that WRKY72 may be directly involved in the defense response signaling pathway while WRKY46 contributes in some other way (Supplemental Figure 13).…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 57%
“…Recent findings concerning the interactions between disease resistance proteins and associated transcription factors (TFs) have provided important insights into the mechanisms governing the transcriptional activation of nuclear R proteins. In rice, the disease resistance protein Pb1 interacts with the transcription factor WRKY45 through its CC domain to protect WRKY45 against degradation by the 26S proteasome, promoting the accumulation of WRKY45 and, presumably, its defense-related transcriptional activity Matsushita et al, 2013). In Arabidopsis, most WRKY genes are implicated in defense (Dong et al, 2003;Chi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a W-box (Eulgem et al, 2000) in the promoter region of OsORAP1 supports this concept. Although no induction of OsWRKY45 was observed in our study, OsWRKY45 might be posttranslationally processed and affect the expression level of downstream genes (Matsushita et al, 2013). Gene expression levels of JA-related genes (OsOPR7, OsJAZ8, and OsJAmyb) suggested that JA production is enhanced in KO.…”
mentioning
confidence: 77%
“…Additionally, WRKYs function in biotic stress tolerance to numerous pathogens (Zheng et al, 2006;Pandey and Somssich, 2009;Ishihama and Yoshioka, 2012;Chen et al, 2013). WRKYs also have been found to be degraded by the 26S proteasome, divulging the role of proteolysis in regulating WRKY TF functions (Matsushita et al, 2012;Yu et al, 2013). The role of WRKYs in plant development, such as trichome and root hair formation, seed coat color, seed size, plant senescence, and male gametogenesis, is also well documented (Johnson et al, 2002;Robatzek and Somssich, 2002;Luo et al, 2005;Guan et al, 2014).…”
mentioning
confidence: 99%